2010
DOI: 10.2478/v10051-010-0004-3
|View full text |Cite
|
Sign up to set email alerts
|

Developing Soft Skills for Engineering: Experience with Student Team Projects

Abstract: Developing Soft Skills for Engineering: Experience with Student Team ProjectsWhile advanced technologies are entering schools at all levels, we claim that other skills required to deal with them in the complex modern world should not be neglected in the education system. In this article, a promising approach to interdisciplinary postgraduate education is described. The idea of the »Team project« course is to give the students the opportunity to gain experience in an extensive project where various skills are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Several authors report different approaches to teaching "soft skills" at engineering schools. Some recently published approaches include network intelligence [10], creativity and collaboration [11], knowledge technologies [12], action research with evaluative features [13], cognitive science [4], and teamwork in action research [14].…”
Section: B Engineering Educationmentioning
confidence: 99%
“…Several authors report different approaches to teaching "soft skills" at engineering schools. Some recently published approaches include network intelligence [10], creativity and collaboration [11], knowledge technologies [12], action research with evaluative features [13], cognitive science [4], and teamwork in action research [14].…”
Section: B Engineering Educationmentioning
confidence: 99%
“…Project-based learning is associated with increased student satisfaction, skill development, and long-term retention of material 15. "Design thinking is a key process that encourages iterative thinking for engineer students as they apply their discipline-specific knowledge to solving real engineering problems" 16 . Involving students in projects intended to focus on designing and physically implementing engineering systems is an endeavor to prepare students for their future work 17. Students involved in project-based-learning reported that these learning methods promoted their critical thinking and problem-solving skills and deepened their interaction with various individuals 18.…”
Section: Literature Reviewmentioning
confidence: 99%